Effect of Coating of Earthed Enclosure and Multi-Contaminating Particles on Breakdown Voltage inside Gas Insulated Bus Duct - Mousa Awad Allah Abd Allah; Sayed Abo El Souad Ward; Amr Ameen EZZ-El Din (Institute of Advanced Engineering and Science, 2014)
Metallic particle contamination is one of the areas of insulation design that are considered critical. This paper demonstrates the control of metallic particles in gas insulated bus duct (GIBD) by using dielectric coating on the inside surface of the outer enclosure of a coaxial electrode system. Several models of GIBD with single and multi-contaminating particles will be studied. In this paper, the Finite Elements Method (FEM) is used to evaluate the electric field distribution on and around single and multi-contaminating wire particles which in contact with dielectric coating of earthed enclosure inside GIBD. The effect of changing the length and the radius of middle particle for multi-contaminating particles on the electric field values are studied. Breakdown Voltage calculations for gas mixtures with single and multi-contaminating wire particles are studied. The effects of gas pressure on the breakdown voltage for various fractional concentrations of SF6-gas mixtures with and without particle contamination and also with and without coating of earthed enclosure are studied. The optimum gas mixture which gives higher dielectric strength with lower cost is also determined. The effect of coating thickness of earthed enclosure on the breakdown voltage for various fractional concentrations of SF6-gas mixtures is also studied. Finally, the effect of length and hemi-spherical radius of multi-contaminating particles on the breakdown voltage with various SF6-gas mixtures and varying gas pressure one time and another time with fixed pressure are studied.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5693